Analysis of Accounting Digitalization, Innovation Orientation, and Collaboration with FinTech on the Performance of Culinary MSMEs in Yogyakarta - Dewi Mariam Widiniarsih; Irwan Irawadi Barus; Ali Nurdin Siregar; Junet Kaswoto; Eko Sudarmanto (West Science Interdisciplinary Studies, 2025)
This study examines the effects of accounting digitalization, innovation orientation, and collaboration with FinTech on the performance of culinary MSMEs in Yogyakarta. Using a quantitative approach, data were collected from 155 MSME owners and managers via a structured questionnaire with a five-point Likert scale. Data analysis was conducted using SPSS version 25, employing descriptive statistics, reliability tests, and multiple regression analysis. The results indicate that accounting digitalization, innovation orientation, and FinTech collaboration each positively and significantly influence MSME performance, with innovation orientation showing the strongest effect. The findings suggest that adopting digital accounting systems, fostering innovative practices, and collaborating with FinTech platforms can enhance operational efficiency, financial management, and overall business performance. These results provide both practical guidance for MSME owners and theoretical insights into factors that drive performance in the culinary sector.